Hack the Business Canvas Model Based on Product-Service System: Natural Language Processing (NLP) Perspective - Eka Sudarmaji; Herlan Masrio; Ismiriati Nasip (Penerbit Goodwood, 2024)
Purpose: This research aims to explore the business model used for energy service companies or ESCOs. Research methodology: This research uses action research based on soft systems methodology and uses business analogies to explore implementing alternative PSS business models. The question component of this research uses the canvas business model (BMC) framework. The use of Natural Language Processing (NLP) from the sub-field of artificial intelligence is used to investigate the problems and concerns of stakeholders about energy efficiency services today. Results: It was found that NLP can extract issues or sentiments about positive or negative aspects when it comes to the development and role of energy service companies in Indonesia. It was also found that PSS's alternative business model can be used as a visual representation of how an energy service company creates, delivers, and adds value to its proportion of customers. Limitations: This research investigated case studies conducted between June 2020 and April 2021 on ESCO company. The findings from this case study may not generalize well to other contexts. Additional case studies on different populations are often needed. Contribution: Due to the increasing demand for energy and limited energy supply, companies can gain a competitive advantage by applying the PSS business model to the energy efficiency industry. Furthermore, there is a vast and untapped market potential for energy service companies in the energy efficiency industry in Indonesia.